PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Ni Putu Yuliana Ria Sawitri; I Wayan Marsa (Warmadewa Management and Business Journal (WMBJ), 2024)
Manufacturing companies are one type of company whose it’s value is greatly influenced by the public's views in carrying out its activities. Company value is an important concept for investors because company value is an indicator of how the market assesses the company as a whole. This research aims to determine the influence of dividend policy, debt policy and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research uses a quantitative design with financial reports and annual reports of manufacturing companies on the IDX as the main data. The population in this research is all manufacturing companies registered on the IDX, amountly 196 companies. The sampling method used purposive sampling, so that the number of samples was determined as 54 companies which made up 162 total observations over 3 years. The main data analysis technique used in this research is multiple linear regression. The research results show that dividend policy, debt policy and profitability have a positive and significant effect on the value of manufacturing companies, both partially and simultaneously. This means that the better the dividend policy, debt policy and profitability, the better the value of the manufacturing company.